Osteochondral repair 3D stent of insulin drug sustained-release microenvironment and preparation method of osteochondral repair 3D stent

A 3D-printed PCL scaffold with PDA modification and insulin-releasing PLGA nanoparticles addresses the limitations of existing scaffolds by enhancing hydrophilicity and biocompatibility, facilitating integrated bone and cartilage repair through controlled drug release.

CN119236170APending Publication Date: 2025-01-03NANJING FIRST HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411375631.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing tissue engineering scaffolds for osteochondral repair, particularly those made of PCL, suffer from poor hydrophilicity, low porosity, single structure, and lack of integrated chondrogenic repair function, failing to meet the needs of simultaneous repair of articular cartilage and subchondral bone.

Method used

A 3D-printed PCL scaffold with a PDA surface modification and PLGA nanoparticles encapsulating insulin, designed for controlled drug release, providing a bionic structure and microenvironment for osteochondral repair.

Benefits of technology

The scaffold supports cell adhesion, proliferation, and differentiation, promoting integrated bone and cartilage repair through controlled insulin release, enhancing hydrophilicity and biocompatibility, and maintaining chondrocyte phenotype.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236170A_ABST
    Figure CN119236170A_ABST
Patent Text Reader

Abstract

The invention discloses an osteochondral repair 3D stent of an insulin drug sustained release microenvironment and a preparation method thereof, the stent is composed of a 3D printed PCL main body stent, a PDA surface modification coating and PLGA nanoparticles wrapping insulin and having drug controlled release efficacy, the diameter of stent fibers of the PCL main body stent is 200 [mu] m, the fiber spacing is 400 [mu] m, and the diameter of the PLGA nanoparticles is 100 [mu] m. The PDA coating is used for surface modification of a PCL main body stent for 3D printing, and the PLGA nanoparticles wrapping insulin are adsorbed on the surface of the stent. The diameter, arrangement, spacing, aperture and porosity of fibers of the stent are controllable, the stent has the characteristic of chondrogenesis stimulation of a drug microenvironment, stem cells are easy to adhere and migrate through PDA modification, cartilage layer cells can be well proliferated in the stent, the cell phenotype can be maintained, more ECM can be generated, and the stent has a good application prospect. And meanwhile, the ingrowth of subchondral bone layer blood vessels and bone tissues is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a 3D scaffold for repairing osteochondrium in an insulin drug sustained-release microenvironment and a preparation method thereof, and belongs to the technical field of medical engineering. Background Art

[0002] Currently, many studies have proposed methods for articular osteochondral regeneration, such as microfracture stimulation, autologous chondrocyte tissue transplantation, stem cell-based therapy, and tissue engineering scaffolds. Although no standardized method has been proven to be very effective, in recent years, the construction of biodegradable tissue engineering scaffolds with a drug microenvironment that promotes cartilage regeneration has brought great hope for improving articular osteochondral repair.

[0003] In recent years, porous scaffolds made of degradable biopolymers have been studied in tissue engineering of various types of tissues, including skin, cartilage, and bone. Moreover, 3D printing technology (Three-Dimensional Printing) has been widely used in clinical work and tissue engineering research. It uses computer-aided design (CAD) digital models to design computer three-dimensional models, thereby providing precise size, shape, structural interconnection characteristics, and precise material composition changes. 3D printed porous scaffolds can provide a structural framework for cell adhesion and extracellular matrix formation. Moreover, 3D printing technology can control the pore size and porosity of porous scaffolds through computer design. The size and shape of the pores are key structural factors for cartilage and bone formation.

[0004] At present, various materials (natural and synthetic) have been used for 3D printing of tissue engineering scaffolds, such as polycaprolactone (PCL), polylactic acid (PLLA), polylactic-co-glycolic acid (PLGA), collagen and gelatin, etc. Since PLLA requires a high printing temperature and a slow degradation rate, and PLGA degrades quickly but has high viscosity and brittleness, it cannot meet the requirements of constructing 3D scaffolds. Therefore, the present invention selects PCL with a moderate degradation rate and good elasticity as the printing material.

[0005] Many studies have confirmed the osteogenic and chondrogenic effects of PCL scaffolds in vitro, but these scaffolds have disadvantages such as poor hydrophilicity, low porosity, single structure, and lack of integrated chondrogenic repair function, which cannot meet the needs of simultaneous repair of articular cartilage and subchondral bone in vivo. In order to improve the hydrophobicity of PCL materials, we need to modify the surface of the scaffolds with PDA (Polydopamine) to greatly improve its hydrophilicity and biocompatibility.

[0006] In summary, the development of a tissue engineering bionic scaffold with low cost, good biocompatibility, induced stem cell directional differentiation, and convenient surgical implantation is of great significance to the development of my country's health industry. Summary of the invention

[0007] The purpose of the present invention is to provide a 3D scaffold for osteochondrosis repair in an insulin drug sustained-release microenvironment and a preparation method thereof, so as to overcome the deficiencies of the prior art.

[0008] To achieve the above object, the technical solution adopted by the present invention is:

[0009] A 3D scaffold for osteochondrosis repair with an insulin drug sustained-release microenvironment, the scaffold is composed of a 3D-printed PCL main scaffold, a PDA surface modification coating, and PLGA nanoparticles that encapsulate insulin and have controlled drug release efficacy.

[0010] Furthermore, the PCL main bracket is made of PCL material, and a bracket body with a regular shape and certain mechanical strength is prepared through computer-aided design and 3D printing technology.

[0011] Furthermore, the diameter of the scaffold fiber of the PCL main scaffold is 200 μm, which is used for cells to easily adhere thereto, and the fiber spacing is 400 μm, which is convenient for chondrocytes and stem cells to grow in.

[0012] Furthermore, the PDA coating is used for surface modification of a 3D-printed PCL main stent, and the PLGA nanoparticles encapsulating insulin are adsorbed on the surface of the stent.

[0013] Furthermore, PLGA nanoparticles encapsulating insulin were prepared by a double emulsion-solvent evaporation method.

[0014] A method for preparing a 3D scaffold for osteochondrosis repair with an insulin drug sustained-release microenvironment comprises the following steps:

[0015] (1) Design the main body and microstructure of the scaffold using EFL-Potato E software;

[0016] (2) 3D printed PCL main scaffold with a fiber diameter of 200 μm and a fiber spacing of 400 μm;

[0017] (3) adding dopamine and the PCL main scaffold to be treated to the Tris buffer solution, placing a magnetic stir bar and stirring in the dark on a constant temperature magnetic heating stirrer, and then drying naturally to obtain a PCL main scaffold modified with PDA surface;

[0018] (4) The drug sustained-release system encapsulating insulin-PLGA nanoparticles was prepared by the double emulsion-solvent evaporation method;

[0019] (5) Add the PCL main scaffold obtained above into the PLGA nanoparticle suspension, and mix well on a decolorizing shaker to obtain the desired 3D scaffold for sustained release of insulin drugs.

[0020] Furthermore, in step (1), the main body and microstructure of the stent are designed using EFL-Potato E software.

[0021] Furthermore, in the step (2), a 3D layered fused deposition modeling printer is used to print the PCL main support.

[0022] Furthermore, in the step (3), dopamine with a final concentration of 2 mg / mL and the PCL main scaffold to be treated are added to a Tris buffer solution with a pH of 8.5, and the solution is stirred in the dark on a constant temperature magnetic heating stirrer for 24 hours before being taken out.

[0023] Furthermore, in step (5), the PCL main scaffold is placed in a PLGA nanoparticle suspension with a final concentration of 3 mg / mL, and the mixture is mixed on a decolorizing shaker for at least 4 hours.

[0024] The beneficial effects of the present invention are as follows:

[0025] (1) Controllable microstructure: The present invention uses 3D printing technology to construct scaffold fibers. Compared with traditional tissue engineering scaffolds, the fiber diameter, arrangement and spacing of the scaffold are controllable. The fiber diameter can be controlled by adjusting the distance between the print head and the platform and the printing temperature, and the fiber arrangement and spacing can be controlled by the EFL-Potato E software design code. The fiber arrangement and spacing can also be adjusted according to different inoculated cells and the required repair tissue.

[0026] (2) Bionic properties: The microscopic physiological properties of the root joint cartilage of the present invention are used to design the scaffold structure. The scaffold fiber diameter is designed to be 200 μm, which is significantly larger than the cell diameter, so that the cells can easily climb on it. The fiber spacing is 400 μm, which is convenient for the adhesion, proliferation and differentiation of chondrocytes and BMSCs. That is, this pore size can make the cartilage layer cells proliferate better in the scaffold, maintain the cell phenotype and produce more ECM, and at the same time facilitate the growth of blood vessels and bone tissue in the subchondral bone layer. The tendon-forming part of the fiber is loaded with a large amount of orderly arranged COL1, and the osteogenic part is loaded with a large amount of hydroxyapatite, so that the structure and composition of the scaffold achieve a bionic effect.

[0027] (3) Insulin drug microenvironment characteristics: Based on the effectiveness of insulin in repairing osteochondral defects, the present invention innovatively prepares PLGA nanoparticles that can sustainably release insulin through poly(lactic-co-glycolic acid) copolymer (PLGA), and loads them on a 3D scaffold with a specific pore size and porosity, thereby making the scaffold have better drug microenvironment chondrogenic stimulation characteristics than traditional scaffolds.

[0028] (4) Integrated bone and cartilage repair: The 3D printed PCL scaffold of the present invention is modified by PDA. The surface modification of PDA greatly improves its hydrophilicity, which is easy for stem cells to adhere and migrate. The specific pore size range can enable cartilage cells to proliferate better in the scaffold, maintain cell phenotype and produce more ECM, while facilitating the growth of blood vessels and bone tissue in the subchondral bone layer. In addition, the osteogenic effect of the insulin drug microenvironment and the ability to promote the maintenance of chondrocyte phenotype ultimately enable the scaffold to achieve the effect of promoting integrated bone and cartilage repair. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of the PCL material 3D layered fused deposition modeling printing platform;

[0030] Figure 2 The three-dimensional (a) and planar design (b) of the EFL-Potato E software support;

[0031] Figure 3 The main body of the printed PCL scaffold and its general morphology after being surface-modified with PDA and loaded with insulin-PLGA nanoparticles;

[0032] Figure 4 SEM, TEM and DLS hydrodynamic size detection of insulin-PLGA nanoparticles;

[0033] Figure 5 Zeta potential detection of insulin-PLGA nanoparticles;

[0034] Figure 6 Drug loading amount (LE) and encapsulation efficiency (EE) detection of insulin-loaded PLGA nanoparticles;

[0035] Figure 7 SEM images of PLGA nanoparticle-PCL scaffolds of insulin (low magnification + high magnification);

[0036] Figure 8 AFM and XPS detection of PDA coating;

[0037] Fig. 9Water contact angle (CA) was used to detect the hydrophilicity of the scaffold;

[0038] Fig.10 Mechanical strength test of the stent;

[0039] Fig.11 Drug release curve detection of insulin-PCL stent;

[0040] Fig.12 CCK-8 and MTT methods were used to detect the proliferation activity of chondrocytes and BMSCs in various parts of the scaffold;

[0041] Fig.13 Live-dead cell staining was used to detect the activity of chondrocytes and BMSCs on the scaffolds;

[0042] Fig.14 Schematic diagram of the surgery for in vivo experimental scaffold implantation in the rabbit articular osteochondral injury animal model. DETAILED DESCRIPTION

[0043] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0044] Example 1

[0045] A 3D scaffold for osteochondrosis repair with an insulin drug sustained-release microenvironment is composed of a 3D printed PCL main scaffold, a PDA surface modified coating, and PLGA nanoparticles that encapsulate insulin and have controlled drug release efficacy.

[0046] The PCL main scaffold is a porous PCL scaffold body with a specific pore size and porosity printed by a 3D layered fused deposition modeling (Fused Deposition Modeling, FDM) printer using 3D printing technology and a melt extrusion method. Among them, the diameter, arrangement and spacing of the scaffold fibers printed using 3D printing technology are controllable. Chondrocytes can proliferate better, maintain cell phenotypes and produce more ECM in scaffolds with a pore size range of 250-500μm, while pore sizes between 400 and 500μm are conducive to the growth of blood vessels and bone tissue. Based on our experience and research, we set the pore size to 400μm to better adapt to the proliferation and differentiation of chondrocytes and BMSCs, thereby promoting the growth of cartilage and bone tissue.

[0047] The 3D scaffold can continuously release insulin, thereby having an osteogenesis effect and promoting the maintenance of chondrocyte phenotype, so as to achieve the effect of bone-cartilage integrated repair.

[0048] The PLGA nanoparticles are prepared by a double emulsion-solvent evaporation method. The PDA coating is applied to the surface modification of the 3D-printed PCL scaffold, and then the PLGA nanoparticles encapsulating insulin are adsorbed onto the surface to make a PCL composite scaffold that can continuously release insulin for the study of osteochondral repair tissue engineering.

[0049] Example 2

[0050] Preparation and application of a 3D scaffold for osteochondrosis repair with an insulin drug sustained-release microenvironment, comprising:

[0051] (1) Preparation of PCL scaffold body: The specific regular macrostructure and microstructure of the scaffold were designed by computer-aided design (CAD) using EFL-PotatoE software. The fiber diameter was 200 μm, the spacing was 400 μm, and the pore angles were 0° / 90° / 180°. A 25-layer composite fiber structure scaffold was printed ( Figure 1 , 2 , 3).

[0052] (2) A 3D layered fused deposition modeling (FDM) printer was used to print the porous PCL scaffold using the melt extrusion method. A certain amount of PCL particles were placed in the printer extrusion chamber in advance and melted into printing slurry at 120°C. During printing, the extrusion chamber and print head temperature were set at 120°C, and the needle movement speed was 4 mm / s. Then, a cylindrical scaffold model was printed layer by layer from bottom to top along the z-axis. Figure 1 , 2 、3)

[0053] (3) Preparation of PLGA nanoparticles encapsulating insulin by double emulsion-solvent evaporation method: 20 mg of recombinant insulin was dissolved in 1 mL of 0.6% (v / v) dilute acetic acid to prepare a 20 mg / mL insulin-dilute acetic acid solution, and 100 ul was taken as the inner aqueous phase; 1% (w / v) polyvinyl alcohol (PVA) solution was prepared, and 1 mL was taken as the outer aqueous phase; 50 mg of PLGA was weighed into a 15 mL centrifuge tube, and 1.25 mL of dichloromethane and 50 μL of Span80, fully ultrasonically mixed as the oil phase; the inner water phase vortex was added to the oil phase, and then ultrasonicated for 3 minutes in an ice bath with an ultrasonic probe at 40% power to form colostrum; then, the colostrum vortex was added to the outer water phase, and then ultrasonicated for 4 minutes in an ice bath with an ultrasonic probe at 40% power to form a double emulsion; then, the double emulsion was transferred to a 50mL beaker, a magnetic stirrer was added, and stirred at a speed of 100rpm on a constant temperature magnetic stirrer overnight; finally, the double emulsion was transferred to a 100KD ultrafiltration tube, ultrafiltered and washed 5 times, and freeze-dried to obtain the prepared PLGA nanoparticles encapsulating insulin, and stored in a refrigerator at 4°C.

[0054] (4) The prepared insulin PLGA nanoparticles were subjected to DLS hydrodynamic size detection and zeta potential detection, and observed by scanning electron microscope (SEM) and transmission electron microscope (TEM). It can be seen that the particle size of blank PLGA nanoparticles is 133.0±46.7nm, and the particle size of insulin-loaded PLGA nanoparticles is 148.1±44.01nm. Figure 4 ) The PDI of blank PLGA nanoparticles was 0.133, while the PDI of insulin-loaded PLGA nanoparticles was 0.115. Both PDI values ​​were less than 0.2, indicating that the particle size distribution of the prepared PLGA nanoparticles in the two groups was uniform. The zeta potential of blank PLGA nanoparticles was -22.7 mV, while that of insulin-loaded PLGA nanoparticles was -23.6 mV.( Figure 5 ).

[0055] (5) Detection of drug loading (LE) and encapsulation efficiency (EE) of PLGA nanoparticles loaded with insulin: First, a UV spectrophotometer was used to perform spectral scanning on the insulin sample (4 mg / mL, dissolved in glacial acetic acid) to determine its UV absorption peak; the scanning results showed that the UV absorption peak of insulin was at 276 nm, and 276 nm was selected as the detection wavelength of insulin; insulin standard curve sample preparation and UV measurement results: 2 mg of insulin solution (10 mg / mL) dissolved in dilute acetic acid was taken and diluted to 1 mL with dilute acetic acid to obtain a 2 mg / mL insulin solution; the 2 mg / mL insulin solution was diluted to 1 mg / mL, 0.5 mg / mL, 0.25 mg / mL, 125 μg / mL, 62.5 μg / mL, 31.25 μg / mL and 15.625 μg / mL in equal proportions to obtain insulin standard solutions of different concentrations. The absorbance of each solution at 276 nm was detected. (Table 1, Figure 6 ).

[0056] Table 1. Absorbance (Abs) detection of insulin standard solutions of different concentrations at 276 nm

[0057]

[0058] After preparing PLGA nanoparticles coated with insulin, the supernatant after the reaction was collected and the volume of the supernatant was recorded. The amount of insulin not encapsulated in the supernatant was detected. The encapsulation rate was calculated according to the amount of insulin fed, and the drug loading was calculated according to its solid content. The calculation formula and results are as follows:

[0059] Insulin encapsulation efficiency (EE) = amount of insulin in PLGA microspheres / insulin feed amount*100%

[0060] =1.426mg / 2000μg*100%=71.30%

[0061] Insulin loading (LE) = amount of insulin in PLGA microspheres / total solid content*100%

[0062] =1426μg / 40000μg*100%=3.57%.

[0063] (6) Physical and chemical characterization of composite scaffolds: PDA coating, water contact angle detection, pore size and porosity detection, mechanical strength detection, and drug release curve detection were performed through macroscopic imaging, SEM, AFM, and XPS.

[0064] In the SEM observation, under low magnification, the four groups of scaffolds all showed a 0°-90° square mesh structure, with uniform pore distribution and a flat surface. There was no significant difference in the morphological structure of the four groups. Under the SEM high magnification microscope, the surface of the PCL scaffold still showed a smooth morphology, while the surface of the PDA / PCL scaffold became rough and had an obvious coating, which was wrapped by uniformly distributed clumps. In addition, the PLGA / PDA / PCL scaffold showed uniformly dispersed PLGA nanoparticles adhered to the PDA clumps. However, there was no obvious morphological and structural difference between the blank PLGA / PDA / PCL scaffold and the insulin-PLGA / PDA / PCL scaffold under the SEM high magnification microscope ( Figure 7 ).

[0065] The surface morphology of the PDA / PCL scaffolds detected by AFM is shown in Figure 2. Figure 8 a. AFM analysis showed that the thickness of the PDA coating layer was 55.64±5.11nm; XPS analysis ( Figure 8 ) showed that the main elements of the PDA surface were carbon (C), oxygen (O) and nitrogen (N), which is consistent with previous reports. AFM and XPS results confirmed that PDA has been successfully coated on the PCL scaffold.

[0066] In the hydrophilicity test, the water contact angle (CA) of the PCL scaffold was 95.42±5.22°, while the CA measured in the PDA / PCL group, blank PLGA / PDA / PCL group and insulin-PLGA / PDA / PCL group was 0°. Fig. 9 It was demonstrated that the surface of the PCL scaffold modified by PDA became highly hydrophilic.

[0067] After freeze-drying, the scaffolds were cut into small pieces, embedded in ethylene glycol methacrylate, and stained with toluidine blue. Pore topology analysis software was then used to detect and calculate the pore size and porosity of each scaffold based on the obtained staining image: PCL scaffold 413.26±25.66μm, PDA / PCL scaffold 416.77±29.21μm, blank PLGA / PDA / PCL scaffold 407.91±27.39μm, insulin-PLGA / PDA / PCL scaffold 418.06±30.17μm. No statistical difference was found.

[0068] The compressive strength of each group of scaffolds prepared was tested using a universal material testing machine. The results showed that the modification of PDA and the adhesion of PLGA nanoparticles had no effect on the mechanical strength of the PCL scaffolds ( Fig.10 ).

[0069] The remaining PLGA nanoparticle suspension after preparing the insulin-PLGA / PDA / PCL composite scaffold was freeze-dried to obtain the content of the remaining PLGA nanoparticles; the total solid content of the prepared 3mg / mL PLGA nanoparticle suspension was subtracted from the content of PLGA nanoparticles to obtain the content of PLGA nanoparticles adhering to the PDA / PCL scaffold (△PLGA content); △PLGA was divided by the number of prepared insulin-PLGA / PDA / PCL composite scaffolds, and multiplied by the drug loading amount (LE) of insulin-PLGA nanospheres to obtain the amount of insulin loaded on each insulin-PLGA / PDA / PCL composite scaffold of 152.38±14.22μg; the insulin-PLGA / PDA / PCL composite scaffold was placed in a dialysis bag, and 1mL of the medium was taken every day to measure the absorbance with a UV spectrophotometer, and the concentration of insulin was calculated based on this. The experimental test was repeated three times, and the test results were averaged. The results were obtained and the release curve was drawn ( Fig.11 ).

[0070] (7) Cytological testing

[0071] The prepared stent was soaked in 75% alcohol for 1 hour and irradiated with ultraviolet light for 2 hours for disinfection.

[0072] CCK-8 and MTT assays were used to detect the proliferation activity of chondrocytes and BMSCs in various parts of the scaffolds. It was found that the cells grew and proliferated well on each group of scaffolds, reflecting the good biocompatibility of the scaffolds ( Fig.12 ).

[0073] Live-dead cell staining was used to detect the activity of chondrocytes and BMSCs on the scaffold, and it was found that the insulin-PCL scaffold proliferated well, reflecting the good biocompatibility of the scaffold and the effect of the insulin drug microenvironment on promoting cell proliferation ( Fig.13 ).

[0074] (8) Animal experiments and in vivo testing

[0075] The prepared 3D insulin-PCL scaffold was surgically implanted into the rabbit joint osteochondral injury animal model ( Fig.14 ).

[0076] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the protection scope of the present invention in any form, and all technical solutions obtained by equivalent replacement and the like fall within the protection scope of the present invention. The parts not involved in the present invention are the same as the prior art or can be implemented by the prior art.

Claims

1. A 3D scaffold for osteochondrosis repair with a sustained insulin drug release microenvironment, characterized in that: The stent consists of a 3D-printed PCL main stent, a PDA surface modification coating, and PLGA nanoparticles that encapsulate insulin and have controlled drug release efficacy.

2. The 3D scaffold for osteochondrosis repair with an insulin drug sustained-release microenvironment according to claim 1, characterized in that: The PCL main bracket is made of PCL material, and a bracket main body with a regular shape and certain mechanical strength is prepared through computer-aided design and 3D printing technology.

3. The 3D scaffold for osteochondrosis repair with insulin drug sustained-release microenvironment according to claim 1, characterized in that: The PCL main scaffold has a fiber diameter of 200 μm, which is used for cells to easily adhere thereto, and a fiber spacing of 400 μm, which is convenient for chondrocytes and stem cells to grow in.

4. The 3D scaffold for osteochondrosis repair with an insulin drug sustained-release microenvironment according to claim 1, characterized in that: The PDA coating is used for surface modification of the 3D-printed PCL main stent, and the PLGA nanoparticles encapsulating insulin are adsorbed on the surface of the stent.

5. The 3D scaffold for osteochondrosis repair with insulin drug sustained-release microenvironment according to claim 1, characterized in that: PLGA nanoparticles encapsulating insulin were prepared by the double emulsion-solvent evaporation method.

6. A method for preparing a 3D scaffold for osteochondrocyte repair with an insulin drug sustained-release microenvironment according to any one of claims 1 to 5, characterized in that: The steps include: (1) Design the main body and microstructure of the scaffold using EFL-Potato E software; (2) 3D printed PCL main scaffold with a fiber diameter of 200 μm and a fiber spacing of 400 μm; (3) adding dopamine and the PCL main scaffold to be treated to the Tris buffer solution, placing a magnetic stir bar and stirring in the dark on a constant temperature magnetic heating stirrer, and then drying naturally to obtain a PCL main scaffold modified with PDA surface; (4) The drug sustained-release system encapsulating insulin-PLGA nanoparticles was prepared by the double emulsion-solvent evaporation method; (5) Add the PCL main scaffold obtained above into the PLGA nanoparticle suspension, and mix well on a decolorizing shaker to obtain the desired 3D scaffold for sustained release of insulin drugs.

7. The method for preparing a 3D scaffold for osteochondrocyte repair with an insulin drug sustained-release microenvironment according to claim 6, characterized in that: In the step (1), the main body and microstructure of the stent are designed using EFL-Potato E software.

8. The method for preparing a 3D scaffold for osteochondrocyte repair with an insulin drug sustained-release microenvironment according to claim 6, characterized in that: In the step (2), a 3D layered fused deposition modeling printer is used to print the PCL main support.

9. The method for preparing a 3D scaffold for osteochondrocyte repair with an insulin drug sustained-release microenvironment according to claim 6, characterized in that: In the step (3), dopamine with a final concentration of 2 mg / mL and the PCL main scaffold to be treated are added to a Tris buffer solution with a pH of 8.5, and the solution is stirred in the dark on a constant temperature magnetic heating stirrer for 24 hours before being taken out.

10. The method for preparing a 3D scaffold for osteochondrosis repair with an insulin drug sustained-release microenvironment according to claim 6, characterized in that: In the step (5), the PCL main scaffold is placed in a PLGA nanoparticle suspension with a final concentration of 3 mg / mL, and the mixture is mixed on a decolorizing shaker for at least 4 hours.